Nucleotide sequence of the haemagglutinin-neuraminidase (HN) gene of a Malaysian heat resistant viscerotropic-velogenic Newcastle disease virus (NDV) strain AF2240 - Tan, W. S.; Lau, C. H.; Ng, B. K.; Ibrahim, A. L.; Yusoff, K. (Informa UK Limited, 1995)
The nucleotide sequence of the haemagglutinin-neuraminidase (HN) gene of Newcastle disease virus (NDV) viscerotropic-velogenic strain AF2240 was determined by direct RNA sequencing and by sequencing RT-PCR products. It encodes a single open reading frame of 581 amino acids with a calculated Mr of 63.8 kDa. The predicted sequence contains five asparagine giycosylation sites. Comparison of the AF2240 HN protein sequence with 13 other previously published sequences showed 88% homology. This HN protein is unique because it lacked the Arg 403 residue which is present in all of the other strains and cannot be grouped under the proposed three size classes of HN proteins in NDV.